Parameters of a gas-solids JET in pneumatic powder injection into liquid alloys with a non-submerged lance - J. Jezierski; K. Janerka (Metalurgija, 2015)
The paper presents powder injection into liquid alloys with a non-submerged lance. The parameters of the diphase gas-solids jet were found as the most important factor to achieve good efficiency of the process. If the parameters are improper, the jet will not penetrate the liquid and the solid particles will not be uniformly distributed. The jet cone profile is often crucial for diphase jet penetration, so this parameter was analyzed along with particle velocity on the lance outlet and the experiments proven this assumption. The use of a high-speed camera allowed to capture and analyze jet motion, which verified the data of previous authors and that in the literature. Experiments of both the model and real injection into molten cast iron proved both the mathematical model and numerical simulation.